Productivity Comparison between Conventional and Islamic Commercial Banks in Indonesia during the COVID-19 Pandemic - Octrina, Fajra; Jamilah, Almi (International Journal of Islamic Economics and Finance (IJIEF), 2024)
This study was conducted to measure and compare the productivity level between conventional and Islamic commercial banks in Indonesia during the COVID-19 pandemic. The number of samples used in this study was 105 banks consisting of 95 conventional banks and 10 Islamic banks. The level of productivity was measured using the Malmquist Productivity Index (MPI) method and Data Envelopment Analysis (DEA) with an intermediation approach, while the productivity of conventional and Islamic commercial banks was compared using normality and different tests. The results showed that the productivity level of the Islamic banks with a Total Factor Productivity Changes (TFPCH) value of 1.001 was driven by technological advances. Meanwhile, the conventional banks were not productive. On the other hand, the results of the different tests showed that there was no significant difference between the productivity level of the conventional and Islamic banks. Conventional banks must enhance innovations in the use of technology in their operational activities to improve their productivity and maintain their high efficiency achievement. Meanwhile, Islamic banks could improve their efficiency in the operational activities so that they would achieve higher productivity and to innovate continually with the use of technology. During the study observation, there was no study comparing between the productivity level of conventional and Islamic commercial banks during the COVID-19 pandemic in Indonesia. Therefore, this research was the first study to discuss the comparison of productivity level between conventional and Islamic commercial banks in Indonesia during the COVID-19 pandemic.